Stink Bug Communication with Multimodal Signals Transmitted through Air and Substrate - Andrej Čokl; Alenka Žunič-Kosi; Raul Alberto Laumann (Ital Publication, 2019)
This review represents complex mechanisms and processes of multimodal communication in stink bugs. During reproductive behavior the airborne and substrate-borne signals enable mate recognition, mediate directionality of movement, eliminate rivals and motivate partners for copulation. Species specific characteristics prevent hybridization at various levels of mating behavior. Male sex and/or aggregation pheromones as uni- or multicomponent signals attract mates to land on the same plant and there, trigger females to call males by vibratory signals, transmitted through the plant. Communication during courtship runs at short distance with visual, airborne, substrate-borne and contact chemical and mechanical signals. Abdomen vibrations produce the main repertoire of female and male calling, courtship and rival vibratory signals. To increase their informational value, stink bugs tune signal frequency, amplitude and temporal characteristics with mechanical properties of plants. The airborne component of species non-specific and high amplitude signals, produced by body tremulation and wing buzzing enables communication contact between mates standing on mechanically isolated plants. Female vibratory signals increase the amount of male emitted pheromone and the latter keeps female calling. Interaction, synergy and characteristics of visual, contact chemical and vibratory signals, exchanged during courtship remain under-investigated. Female and male competition for access to copulation in imbalanced sex conditions is characterized by duetting with rival song vibratory signals. Different receptors in and on different parts of the body are able to detect with high sensitivity multimodal airborne and substrate-borne communication signals. The relevance of the multimodal communication for the reproductive success of stink bugs is discussed.